Causes and consequences of ontogenetic dietary shifts: a global synthesis using fish models. (24th September 2018) - Sánchez‐Hernández, Javier; Nunn, Andy D.; Adams, Colin E.; Amundsen, Per‐Arne
ABSTRACT: Ontogenetic dietary shifts (ODSs), the changes in diet utilisation occurring over the life span of an individual consumer, are widespread in the animal kingdom. Understanding ODSs provides fundamental insights into the biological and ecological processes that function at the individual, population and community levels, and is critical for the development and testing of hypotheses around key concepts in trophic theory on model organisms. Here, we synthesise historic and contemporary research on ODSs in fishes, and identify where further research is required. Numerous biotic and abiotic factors can directly or indirectly influence ODSs, but the most influential of these may vary spatially, temporally and interspecifically. Within the constraints imposed by prey availability, we identified competition and predation risk as the major drivers of ODSs in fishes. These drivers do not directly affect the trophic ontogeny of fishes, but may have an indirect effect on diet trajectories through ontogenetic changes in habitat use and concomitant changes in prey availability. The synthesis provides compelling evidence that ODSs can have profound ecological consequences for fish by, for example, enhancing individual growth and lifetime reproductive output or reducing the risk of mortality. ODSs may also influence food‐web dynamics and facilitate the coexistence of sympatric species through resource partitioning, but we currently lack a holistic understanding of the consequences of ODSs for population, community and ecosystem processes and functioning. Studies attempting to address these knowledge gaps have largely focused on theoretical approaches, but empirical research under natural conditions, including phylogenetic and evolutionary considerations, is required to test the concepts. Research focusing on inter‐individual variation in ontogenetic trajectories has also been limited, with the complex relationships between individual behaviour and environmental heterogeneity representing a particularly promising area for future research.